ANALISIS KADAR LEMAK TOTAL PADA BUAH SALAK MERAH (Salacca edulis) DI NEGERI RIRING DAN NEGERI BURIA KECAMATAN TANIWEL KABUPATEN SERAM BAGIAN BARAT - Manuhuttu, Debi Lisa; Smith, Alwi; Salmanu, Sriyanti Imelda Aksamina; Simal, Rufiati (Program Studi Pendidikan Biologi FKIP Unpatti, 2025)
Background: In Maluku Province, especially in West Seram Regency (SBB) Taniwel District, salak plants were found with unique thick yellow flesh with a red tinge, called red salak. Negeri Riring and Negeri Buria are samples of red salak cultivation centers that are at different altitudes, allowing for differences in primary metabolite content, especially total fat content in red salak plants. Methods: Analysis of total fat content was carried out in several stages, namely, the red salak fruit preparation stage where the skin and flesh of the salak fruit were peeled and separated. After that, the sample was dried in an oven for 6x24 hours and ground into powder. The total fat content test stage used the Soxhlet method, where this stage produced a solution used to calculate the total fat content. Results: The results of the study showed that red salak fruit contained Negative Total Fat in both locations at different altitudes. The highest fat content in red salak fruit was obtained at 0.54995% in Negeri Buria. Meanwhile, the lowest fat content in red snake fruit was obtained at 0.52935% in Negeri Riring. Conclusion: different growing altitudes affect the total fat content in red snake fruit, where the higher the growing location, the lower the fat content, which is also supported by several internal and external factors.